Nilai Estetika dan Kearifan Lokal dalam Tradisi Bantengan: Sebuah Kajian Budaya - Cindy Ayu Dwi Amiarti; Didik Sukriono; A. Rosyid Al Atok; Siti Awaliyah (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2026)
The Bantengan tradition in East Java functions not only as an aesthetic performance but also as a medium for preserving local wisdom that is currently facing pressures from modernization, commodification, and generational gaps. This study aims to analyze the interaction between aesthetic dimensions and local wisdom in Bantengan, as well as to reveal the dynamics of meaning transformation and sustainability challenges in the contemporary era. This study employs a descriptive qualitative approach with a cultural studies design. Data were collected through participatory observation, in-depth interviews with seven key informants (artists/pawang, traditional leaders, studio managers, and cultural officials) in Malang Regency and Batu City, as well as performance archive documentation. Data analysis applied the interactive model with source and technique triangulation to ensure the validity of findings. The results show that the aesthetic values of Bantengan are manifested in the synergy of kinesthetic movement, gamelan rhythm, and costume symbolism that functions as a medium of collective communication. Local wisdom is reflected in the mechanisms of mutual cooperation (gotong royong), spiritual rituals (nyuguh/nyamuk), and character pedagogy through symbolic combat narratives. However, this tradition faces serious challenges in the form of meaning shifts due to market logic (commodification), declining participation of the younger generation, and friction between sacred dimensions and demands for contemporary entertainment. These findings emphasize the need for adaptive preservation strategies that combine community autonomy, regional regulation, and digital documentation. Theoretically, this article contributes to cultural studies by providing a critical analytical framework regarding the negotiation of aesthetic-local wisdom meanings amid modernization pressures.